Does the aerobic threshold correlate with the maximal fat oxidation rate in short stage treadmill tests? - Peric, R.; Meucci, M.; Bourdon, P. C.; Nikolovski, Z. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: The aim of this study was to identify the exercise intensity that elicited the highest rate of fat utilization (FATmax) and to assess its relationship with the aerobic threshold (AeT) in male athletes. We hypothesized existence of high correlation of these two parameters when a short-staged graded treadmill test with AeT identified through breath-by-breath gas exchange analysis was used. METHODS: Fifty-six trained male athletes (age 25.6±3.4 y, height 197.8±5.6 cm, body mass 98.5±6.6 kg) participated in the study. Pearson correlation coefficient (r) and effect size (R2) were used to evaluate the existence of connection between VO2 at AeT and at FATmax. Maximal oxygen consumption (VO2max) and substrate oxidation were determined using breath-by-breath indirect calorimetry during a short-staged graded treadmill test to exhaustion. RESULTS: Mean VO2max was 52.12±9.02 mL/kg.min. FATmax and AeT occurred at 47.47±10.59% of VO2max and 45.95±10.21% of VO2max, respectively. Fat utilization at FATmax was 0.59±0.24 g/min. A high correlation was found between VO2 at FATmax and at AeT (r=0.88, P<0.01, 95% CI: 0.80 to 0.93). The effect size was 77.44%. CONCLUSIONS: Our results confirm the hypothesis of an existence of a high correlation between AeT and FATmax allowing implementation of more accurate training approach.